Combined ACL-Posterolateral Corner Injury in a Skeletally Immature Athlete - Mascarenhas, Randy; Bonci, Gregory; Bowman, Karl F.; Forsythe, Brian; Harner, Christopher D. (The Journal of Knee Surgery, 2013)
Combined injury to the anterior cruciate ligament (ACL) and posterolateral structures of the knee is a rare yet increasingly recognized clinical entity. In children or adolescents with open growth plates, this injury pattern is considered to be even more rare than in adults. Because knee ligaments are felt to be stronger than the adjacent physeal plates, the energy of pathologic translational and rotatory stress commonly results in fracture or avulsion injuries rather than ligamentous injury. The appropriate treatment for either injury remains controversial in the skeletally immature patient, with no previously reported case of this combined injury pattern in a patient with open physes. We present a case of a 12-year-old boy who sustained an ACL-posterolateral corner injury while playing football, and subsequently underwent acute repair of the posterolateral structures with a plan to perform ACL reconstruction at a later date.
Keywords: ACL; pediatric; posterolateral corner; athlete